PHARMACEUTICAL AND ANALYTICAL STANDARDIZATION OF RASAPACHAK VATI (TABLET) - Ambadkar Shruti; Belge Raman; Deshpande Sarang; Gadkari Kishore; Pable Tarun (International Journal of Applied Ayurved Research, 2017)
In Ancient Ayurvedic texts, many formulations are mentioned that are effective differently on different diseases depending upon the properties and qualities of the constituents may be of plant, mineral or herbal origin. Medicines prepared using traditional method may not have the desired quality, batch to batch consistency. Hence, there is a need of standardization of these raw materials used and its standard operating procedures as per scientific parameters in today’s era to prevent use of spurious drugs and increase the standard of the final product. Charakacharya have mentioned Rasapachak Yoga in Jwarachikitsa adhayay of Charak Samhita for all the dhatugat jwar, wherein Rasapachak yoga for the treatment of Rasagat Jwar i.e. Santat jwar(~ continuous fever). Ayurveda physicians prescribe this Yoga in kwatha, churna, etc. forms as per the convenience which results in dose variation and affect the efficacy of the medicine. Hereby, to avoid batch to batch variation, changes in its friability, disintegration time, etc. and to increase the dose accuracy and palatability, an effort has been made to standardize the raw materials and the dosage form of the final product has been changed to tablet form. As no significant information regarding standardization of this yoga is available, this study can be referred for further pharmaceutical processes.